Revisiting public diplomacy in a postpandemic world: The need for a humanity-centered communication logic. Issue 1 (March 2022) - Zaharna, R S; Huang, Zhao Alexandre
Professor R. S. Zaharna is a leading scholar in international communication and public diplomacy. She has witnessed the rapid development of public diplomacy since 2001 and has been committed to researching different communication logics in public diplomacy. In recent years, she has begun to explore the boundaries of public diplomacy theory, aiming to expand the conceptual scope of public diplomacy, advocating a relational shift in conventional public diplomacy studies, and reflecting on the limitations of the actor-centered approach in international communication. In this interview, Professor Zaharna shared her definition of public diplomacy and discussed how relations, connectivity, and interactivity will be indispensable in public diplomacy research and practice. She also analyzed the limitations of the actor-centered public diplomacy research and explained three communication logics in humanity-centered diplomacy. For her, humanity-centered public diplomacy responds to the needs of human societies, harnessing our capacity to collaborate in collective decision-making and problem-solving. In this case, communication is not about agency or control but about navigating the connectivity and interactivity made possible by digitalization, emphasizing horizontal social collaboration, and observing relational constellations and dynamics.